REALIZATION OF DISAGREEMENT STRATEGIES BY INDONESIAN SPEAKERS - Wildan Nurul Aini (University of Kuningan, 2015)
Abstract: This study investigates the realization of disagreement strategies employed by Indonesian speakers. The strategies are then related to the interlocutor’s level of power. The data is collected using DCT Type B adapted from Azis (2000) and analysed using adapted disagreement strategies from Muntigl and Turnbull (1998) and Chen (2006). The results shows that Indonesian speakers tend to use different disagreement strategies to different level of power of the interlocutor. To the interlocutor with the higher power (the superior), the speakers tend to use counterclaims and no disagreement strategies. In addition, to the speakers with the same level of power, the contradiction strategy is preferred. In the meantime, to the interlocutor with the lower level of power, the speakers are likely to choose challenge. These various selections of disagreement strategies are also influenced by concept of FTAs of Brown and Levinson (1987).Keywords: disagreement, power, face, FTAs